2008
DOI: 10.1111/j.1365-2249.2008.03748.x
|View full text |Cite
|
Sign up to set email alerts
|

B cells are involved in the modulation of pathogenic gut immune response in food-allergic enteropathy

Abstract: Summary Food enteropathies involve uncontrolled or hypersensitivity reactions to ingested nutrients and may result in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 38 publications
1
4
0
3
Order By: Relevance
“…Similar results were obtained by others in BALB/c mice orally sensitized with CMP or peanut [34]. In the same sense, Cardoso et al [3], in a food allergy mouse model developed in C57BL/6 mice, showed that skin sensitization with peanut and alum induced a gut-inflammatory response after feeding mice with peanuts. Although they found a significant induction of IL-4 and IL-13, no increase in IL-5 and IFN-γ was detected.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Similar results were obtained by others in BALB/c mice orally sensitized with CMP or peanut [34]. In the same sense, Cardoso et al [3], in a food allergy mouse model developed in C57BL/6 mice, showed that skin sensitization with peanut and alum induced a gut-inflammatory response after feeding mice with peanuts. Although they found a significant induction of IL-4 and IL-13, no increase in IL-5 and IFN-γ was detected.…”
Section: Discussionsupporting
confidence: 72%
“…These models have unveiled different aspects of mucosal immunity that occur after the breakdown of oral tolerance to ingested nutrients [1,2]. They have evolved from systemic to mucosal sensitization protocols with the consequent induction of anaphylaxis-like IgE-mediated reactions that mimics the human disease upon allergen challenge [3,4,5]. Due to the immune tolerance to antigens encountered in the gastrointestinal mucosa [6], adjuvants are commonly used to abrogate this complex and not fully understood process [7].…”
Section: Introductionmentioning
confidence: 99%
“…), one patient with c.667G>T and one patient with c. 1384G>T [72] have somatic mosaicisms of cells with the mutated CYBB sequence and a small proportion of reverse mutated cells with the wild-type CYBB sequence. …”
Section: Tablementioning
confidence: 99%
“…To test this hypothesis, follicular B cells should be isolated and activated with or without bortezomib treatment, and then analyzed in more detail with respect to proliferation and isotype switching ex vivo. Furthermore, previous data indicated that B-cell-deficient mice have less allergen-induced diarrhea than wild-type mice, followed by less plasma cell accumulation in the intestine [33,34]. Interestingly, blocking of CD23 with anti-CD23 completely abolished the antigen uptake in sensitized mice.…”
Section: Discussionmentioning
confidence: 89%